METABOLIC SYNDROME: IN VITRO ANTIOXIDANT, ANTICANCER, ANTI-INFLAMMATORY AND ANTIMICROBIAL ACTIVITIES OF DISSOTIS ROTUNDIFOLIA (SM.) WITH PHYTOCHEMICAL AND NUTRITIONAL COMPONENTS - GBADAMOSI, Idayat Titilayo; BADEJO , Joseph Ayotunde; AJIBADE, Temitayo Olabisi; AGBATUTU , Akpevwoghene; ABIARA , Ezekiel Ayodeji; AKINKOYE , Akinlolu Tobi; YEYE , Emmanuel Oloruntoba; FAMUYIDE , Ibukun Micheal; MCGAW , Lyndy Joy; NKADIMENG , Sanah Malomile; OYAGBEMI , Ademola Adetokunbo; OMOBOWALE , Temidayo Olutayo; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2024)
Background: Dissotis rotundifolia (Sm.) Triana is a prostrate herb of the family Melastomataceae. It is used for the treatment of obesity, hypertension, circulatory problems and metabolic syndrome (MS). This study evaluated the antioxidant, anticancer, anti-inflammatory.and antimicrobial activities of the whole plant of D. rotundifolia to validate its therapeutic potential in the management and treatment of MS. Materials and Methods: The plant was screened for proximate, mineral, vitamin and phytochemical components, as well as antioxidant activities using standard laboratory techniques. The anticancer activities of the ethanol plant extract were against kidney (VERO) and breast (MCF-7) cancer cells. The anti-inflammatory activity of the extract was determined using nitric oxide production inhibition assay and the antimicrobial activity was evaluated against five pathogenic organisms. All data were subjected to statistical analysis. Results: The plant was rich in carbohydrate (47.87%), protein (22.5%), crude fibre (9.57%), Na (206.67mg/100g), Ca (183.33mg/100 g), vitamin C(25.53mg/100g), flavonoids (685.00mg/100g), alkaloids (616.67 mg/100g) and saponins (471.67 mg/100 g) contents. The extract exhibited considerable and varied antioxidant activities. The plant extract was very active against VERO and MCF-7 cells at low concentrations (0.145 mg/ml and 0.141 mg/ml respectively) compared to doxorubicin. It also exhibited significant anti-inflammatory action against lipopolysaccharide (LPS)-stimulated RAW macrophage. The extract was active against all test organisms. Overall, D. rotundifolia displayed significant antioxidant, anticancer, anti-inflammatory and antimicrobial activities. Conclusion: The observed bioactivities of the plant could be attributed to its phytocontents and are indications of its potential as an agent for the management and treatment of metabolic syndrome.